The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/17480272.2014.977944
|View full text |Cite
|
Sign up to set email alerts
|

Optimization potential for perception-oriented appearance classification by simulated sawing of computed tomography-scanned logs of Norway spruce

Abstract: Wood, as a natural material, has favourable properties in both technical and aesthetic aspects. Due to its inherent variability, production of high-quality sawn timber demands adequate control of log conversion, which is feasible with computed tomography (CT) log scanning. Existing appearance grading rules for sawn timber might not fully reflect people's visual perception of wood surfaces, and therefore, an alternative, more perception-oriented appearance classification could be beneficial. An appearance class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This, in combination with the ever-increasing consumption of wood because of a growing population, can lead in the coming years to the lack of a positive balance between the annual volumetric growth and consumption of wood 3 . Projected and actual scarcity of the raw material (logs) availability, increasing competition on the international market, combined with significant and ever-growing production costs compel wood processing plants to dramatically modernize their technologies 4 , 5 . An important innovation toward increasing environmental and economic sustainability of timber production is to reduce the volume of wood residues by minimizing the sawing kerf.…”
Section: Introductionmentioning
confidence: 99%
“…This, in combination with the ever-increasing consumption of wood because of a growing population, can lead in the coming years to the lack of a positive balance between the annual volumetric growth and consumption of wood 3 . Projected and actual scarcity of the raw material (logs) availability, increasing competition on the international market, combined with significant and ever-growing production costs compel wood processing plants to dramatically modernize their technologies 4 , 5 . An important innovation toward increasing environmental and economic sustainability of timber production is to reduce the volume of wood residues by minimizing the sawing kerf.…”
Section: Introductionmentioning
confidence: 99%
“…For the live and cant sawing schemes, the CP assignment decision is done using two approaches. In the first approach, the CPs are selected based on the logs' top-end or butt-end diameters, see for example Nordmark and Oja (2004), Fredriksson (2014), Breinig et al (2015) and Ah Shenga et al (2016). In the second approach, the log is examined for all or a subset of CPs to select the one that results in a higher yield, see for example Pereira and Usenius (2006), Thomas (2012), Riesco Muñoz et al (2013, Ursella et al (2018) and Khaloian Sarnaghi et al (2020).…”
Section: Usage Of Predefined Cut Patternsmentioning
confidence: 99%
“…Relatable to the studies Lycken andOja (2006), Berglund et al (2015), Olofsson et al (2019a), andBreinig et al (2015b) performed cluster analysis and classification of floor boards according to their subjective visual characteristics, showing the possibility to use a set of knot descriptive variables to group floor boards into homogeneous clusters with significant differences. Furthermore, in a continuation study, Breinig et al (2015a) used simulated sawing of CT-scanned logs to optimise the rotational angle of the logs to yield the most number of floor boards of cluster-grades defined as in the previous study. Both studies showed the potential to use machine learning methods, in particular PLS, to appearance grade sawn timber by their holistic-subjective appearance.…”
Section: Introductionmentioning
confidence: 99%